2016
DOI: 10.1039/c6ra17770k
|View full text |Cite
|
Sign up to set email alerts
|

Isoliquiritigenin and liquiritin from Glycyrrhiza uralensis inhibit α-synuclein amyloid formation

Abstract: Bioactive isoliquiritigenin and liquiritin inhibit α-synuclein aggregation and extend the life span of the C. elegans model of Parkinson's disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 48 publications
0
10
0
Order By: Relevance
“…G. uralensis is one of the main herbs in approximately 40% of traditional medical prescriptions described in pharmacopeias for the treatment of PD. ILG showed inhibitory effects against membrane toxicity in in vitro aggregated α-syn and disaggregated preformed mature fibrils in a transgenic Caenorhabditis elegans PD model ( Liao et al, 2016 ).…”
Section: Pharmacological Activities Against Nddsmentioning
confidence: 99%
“…G. uralensis is one of the main herbs in approximately 40% of traditional medical prescriptions described in pharmacopeias for the treatment of PD. ILG showed inhibitory effects against membrane toxicity in in vitro aggregated α-syn and disaggregated preformed mature fibrils in a transgenic Caenorhabditis elegans PD model ( Liao et al, 2016 ).…”
Section: Pharmacological Activities Against Nddsmentioning
confidence: 99%
“…Additionally, previously established methods by Shan et al applied liquid–liquid extraction which requires acidification with HCl for the extraction of glycyrrhizin and glycyrrhetinic acid and a larger plasma sample volume (100 μL) and the LLOQs for glycyrrhizin and three flavones were 1 and 0.34–0.5 ng/mL, respectively [19]. Herein, we used a protein-precipitation method with methanol containing IS rather than a previously described liquid–liquid extraction method or sample preparation via evaporation and reconstitution method [8,17,19], and then directly injected an aliquot of the supernatant after centrifugation of protein-precipitated plasma samples.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, glycyrrhizin is commonly used owing to its therapeutic effects against arthritis, hepatotoxicity, leukemia, allergies, stomach ulcers, and inflammation. Moreover, the major active flavonoids of Glycyrrhizae Radix, such as isoliquiritigenin, liquiritin, and liquiritigenin [8], are often used as anti-depressants or as anticancer, cardio-protective, anti-microbial, and neuroprotective agents [9,10,11,12,13,14]. Based on the literature search, glycyrrhizin, isoliquiritigenin, liquiritin, and liquiritigenin were selected as predominant or pharmacological components of GRE.…”
Section: Introductionmentioning
confidence: 99%
“… EC 50 /IC 50 Other targets Status Ref. Antibiotics Glucosides 21 EC 50 = 6.96 μM Aβ, tau a [ 103 , 105 ] 51−53 N/A N/A a, a, b [ 137 139 ] 22 EC 50 = 6.06 μM a [ 105 ] Quinones Dopamine and its analogs 54 IC 50 = 30 μM N/A a [ 140 ] 23 IC 50 = 7.1 μM Aβ, tau a [ 105 , 106 , 109 ] 55 IC 50 = 29 μM N/A a [ 140 ] 24−28 N/A N/A a [ 108 ] 56 IC 50 = 18 μM N/A a [ 140 ] Dyes and pigments 57 IC 5 0 = 15 μM N/A a [ 140 ] 29 IC 50 = 14.7 μM Aβ, tau a [ 109 ] 58−59 …”
Section: Small Molecule Inhibitors Against α-Synuclein Aggregationmentioning
confidence: 99%
“…In vitro studies have demonstrated that compound 53 can inhibit both oligomerization and fibrillation of α-syn. In a transgenic C. elegans expressing human α-syn, compound 53 significantly inhibited α-syn aggregation and extended the life span of the treated worms [ 139 ].…”
Section: Small Molecule Inhibitors Against α-Synuclein Aggregationmentioning
confidence: 99%